Examining the impacts of technological advancement on cereal production in ASEAN countries: Does information and communication technology matter? - Chandio, Abbas Ali; Gokmenoglu, Korhan K.; Sethi, Narayan; Ozdemir, Dicle; Jiang, Yuansheng (Elsevier, 2023)
In this study, we examine the effects of technological development (via fertilizer and pesticide consumption) and information and communication technology (ICT) on cereal production in four ASEAN countries (Indonesia, Malaysia, the Philippines, and Thailand) from 1991 to 2018. For empirical investigation, this study used advanced econometric methodologies. The estimated results demonstrate the long-run co-integration relation-ship between the variables. Pooled mean group (PMG)-based empirical results show that technological devel-opment (via fertilizer consumption and pesticide use) significantly increases cereal production in the long-run after confirming the long-run association among the variables of interest. Similarly, ICT also significantly en-hances cereal production in the long-run. It has been thoroughly demonstrated that technological development and ICT play an important role in increasing cereal production and ensuring food security in the selected ASEAN countries. Furthermore, the findings of the Dumitrescu-Hurlin (D-H) causality test show unidirectional causality from fertilizer consumption and pesticide use to cereal production, as well as bidirectional causality between ICT and cereal production. In this regard, it is critical for local farmers to produce high added value through tech-nological development while also serving as a regional base and supply center in agriculture. To ensure that technological innovations enhance productivity, ICT-based agriculture, and the adoption of technology in the production of agricultural products, governments should promote locally sustainable ICTs, such as mobile phones and Internet-based digital tools and services.
Keywords: Cereal production; Technological development; ICT; ASEAN countries